Use of the whirligig principle for stabilizing the initial states of some classic and quantum systems - Buts, V.A. (Вопросы атомной науки и техники, 2020)
It is shown that the whirligig principle can be used for stabilization of the initial states of some classical and quantum systems. This feature of the whirligig principle is demonstrated by simple examples. The most important result of this work is the proof of the fact that the stabilization of the excited states of quantum systems can be realized by acting not on the quantum system itself, but by acting on the states into which the system must go. Potentially, this result can be used to stabilize excited nuclear systems. Показано, що принцип дзиґи може бути використаний для стабілізації вихідних (початкових) станів деяких класичних і квантових систем. Така особливість принципу дзиґи продемонстрована на простих прикладах. Найбільш важливим результатом роботи є доказ факту, що стабілізацію збуджених станів квантових систем можна реалізувати впливом не на саму квантову систему, а впливаючи на стани, в які система повинна перейти. Потенційно цей результат може бути використаний для стабілізації збуджених ядерних систем. Показано, что принцип юлы может быть использован для стабилизации исходных (начальных) состояний некоторых классических и квантовых систем. Такая особенность принципа юлы продемонстрирована на простых примерах. Наиболее важным результатом работы является доказательство факта, что стабилизацию возбужденных состояний квантовых систем можно реализовать воздействием не на саму квантовую систему, а воздействуя на состояния, в которые система должна перейти. Потенциально этот результат может быть использован для стабилизации возбужденных ядерных систем.